Job Displacement, Inter-Regional Mobility and Long-Term Earnings - Terhi Maczulskij; Petri Böckerman; Tuomas Kosonen (Institute of Labor Economics (IZA), 2018)
We examine the effect of job displacement on regional mobility using linked employer-employee panel data for the 1995-2014 period. We also study whether displaced movers obtain earnings and employment gains compared to displaced stayers. The results show that job displacement increases the migration probability by ~70%. However, social capital in a region and housing characteristics decrease the propensity to move, indicating that people do not make the migration decisions solely based on short-term economic incentives. Migration has an immediate negative relationship with earnings, but the link diminishes as time passes and eventually turns positive for men. The link between migration and employment is nevertheless positive and persistent for both genders.
Keywords: J61; J63; 330; unemployment; job displacement; migration; earnings; employment